2015
DOI: 10.1159/000437230
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus in Metastatic Breast Cancer: Clinical Experience as a Late Treatment Line

Abstract: Background: Everolimus (Afinitor®) plus exemestane are indicated for hormone receptor-positive, HER2/neu-negative metastatic breast cancer (MBC), in menopausal women without symptomatic visceral disease after recurrence or progression following aromatase inhibitors. But everolimus efficacy as late treatment has not been explored. Methods: Sixty-three MBC patients progressing under hormonotherapy (HT; n = 30) or after chemotherapy (CT; n = 32) received everolimus plus HT (EHT) and were analyzed for safety, effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In this study, the median TTF in unelected patients was 5.2 months, which is similar to that reported in previous real-world cohort studies (4.0-5.7 months). 1315 The shorter treatment duration compared to that in the BOLERO-2 trial can be attributed to the high proportion of heavily treated patients in our study (ie, 14.2% of patients had PS 2 or 3 and 53.7% of patients had more than 4 previous treatments of EVE). The reason why EVE was administered to more than half of the patients with the later treatment line was that EVE was used immediately after being approved to the later line patients who had been waiting for this drug in this cohort.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In this study, the median TTF in unelected patients was 5.2 months, which is similar to that reported in previous real-world cohort studies (4.0-5.7 months). 1315 The shorter treatment duration compared to that in the BOLERO-2 trial can be attributed to the high proportion of heavily treated patients in our study (ie, 14.2% of patients had PS 2 or 3 and 53.7% of patients had more than 4 previous treatments of EVE). The reason why EVE was administered to more than half of the patients with the later treatment line was that EVE was used immediately after being approved to the later line patients who had been waiting for this drug in this cohort.…”
Section: Discussionmentioning
confidence: 74%
“…One of the interesting results is that in the multivariate analysis, dose reduction from any initial dose of EVE was associated with a longer TTF. Pouget et al 13 also showed that patients with dose adaptation tended to have a longer TTF in their cohort study. The reason by which dose reduction is correlated with a longer TTF is uncertain.…”
Section: Discussionmentioning
confidence: 80%
“…There is an increasing number of patients under treatment, for increasingly longer periods (Ferlay et al, 2013). However, current treatments for metastatic breast cancer seldom lead to patients' recovery (French NCI, 2014;Pouget et al, 2015). They usually have the effect of delaying the progression of cancer, reducing symptoms and improving the patients' quality of life (Maher, 2014;Piccart et al, 2014).…”
mentioning
confidence: 99%